Aged Care Assessment Service practitioners: A review of current practice for assessment of cognition of older people of culturally and linguistically diverse backgrounds in Victoria. (13th September 2013) - Vrantsidis, Freda; LoGiudice, Dina; Rayner, Victoria; Dow, Briony; Antonopoulos, Stephanie; Runci, Susannah; O'Connor, Daniel W.; Haralambous, Betty
<x xml:space="preserve">Abstract</x> Aim This paper describes current practices and gaps identified by Aged Care Assessment Service (ACAS) clinicians in the assessment of cognition of clients of culturally and linguistically diverse (CALD) background in Victoria. Method A web‐based survey, exploring practices and challenges faced by clinicians in assessing CALD clients and their families, was sent to all Victorian ACAS managers to distribute to their teams. Three focus groups were also conducted with ACAS clinicians to further explore these issues. Results Seventy‐nine web‐based surveys were returned and 21 ACAS clinicians attended a focus group. Challenges reported included the availability and quality of interpreters, and variability in training received and confidence in assessing cognitive impairment in CALD clients. Conclusion ACAS clinicians reported that assessment of cognition for those of CALD background was challenging. Based on this feedback, practice tip sheets were developed as educational aids to assist ACAS staff.